Digital AgroMet advisory platform for resilient agriculture in Ethiopia - International Center for Tropical Agriculture; International Maize and Wheat Improvement Center; Ethiopian Institute of Agricultural Research (CGIAR System Organization, 2019)
Poster prepared for a share fair, Addis Ababa, May 2019